Pokhorony K. U. Chernenko . Pokhorony K. U. Chernenko . Funeral of K.U. Chernenko . Похороны К. У. Черненко - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by the state television (Moscow) in the USSR and recorded by the Radio Liberty Monitoring Unit in Munich as part of their effort to track and analyze the official media of the republics of the Soviet Union. Передача государственного телевидения (Москва, СССР) была записана отделом мониторинга радиостанции Свобода (Мюнхен) как часть проекта по анализу официальных средств информации республик Советского Союза. Broadcast of the funeral ceremony. Featured in the program: Gorbachev, Mikhail Sergeevich (General Secretary of the Central Committee of the CPSU) Трансляция церемонии похорон. В программе участвуют: Горбачев, Михаил Сергеевич (Генеральный секретарь ЦК КПСС)